New media in promoting government programs - Negizbayeva, M.O.; Slyamova, А.С.; Zhui, Ли (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The definition of technologies of the traditional and civil media in realizing the idea of New Kazakhstan presents itself an objective necessity and urgency of the research. To accumulate knowledge, skills, experience and to create an effective algorithm for the further action of traditional and new MMC on the modernization of public consciousness and spiritual-moral revival, which forms the framework of national identity and will allow Kazakhstan to follow its own, sustainable, qualitative and perspective path. The purpose of this article is influence on the concept of development of the domestic media sphere, strengthen the integration of state mechanisms in informing young people and its involvement in the process of building a new Kazakhstan. The scientific and practical value. The results can be used to form a package of recommendations and proposals for improving the state information policy and organizing new media resources. Methodology of the research is carried out using a set of modern methods of scientific knowledge, including both general research methods and private-scientific methods, as well as an interdisciplinary approach. In the course of the analysis of the indicated topic, theoretical approaches based on the axioms of foreign scientists along with such empirical methods as description, control, and comparison were used. To determine the concept and structure of the New strategy information activity in the field of traditional and new media in Kazakhstan and its effective influence on the spiritual growth of people of Kazakhstan, it is important to understand the practical significance of this study. Today, there is a decline in the interest of new and social media in the issues of ideological education and support of the state’s efforts in the spheres of social and state construction, and meanwhile a significant part of Kazakhstan’s youth is a constant spectator or a reader of new media.